Klotho Lacks an FGF23‐Independent Role in Mineral Homeostasis. (17th July 2017) - Andrukhova, Olena; Bayer, Jessica; Schüler, Christiane; Zeitz, Ute; Murali, Sathish K; Ada, Sibel; Alvarez‐Pez, Jose M; Smorodchenko, Alina; Erben, Reinhold G
ABSTRACT: Fibroblast growth factor‐23 (FGF23) is a bone‐derived hormone regulating vitamin D hormone production and renal handling of minerals by signaling through an FGF receptor/αKlotho (Klotho) receptor complex. Whether Klotho has FGF23‐independent effects on mineral homeostasis is a controversial issue. Here, we aimed to shed more light on this controversy by comparing male and female triple knockout mice with simultaneous deficiency in Fgf23 and Klotho and a nonfunctioning vitamin D receptor (VDR) ( Fgf23 / Klotho /VDR) with double ( Fgf23 /VDR, Klotho /VDR, and Fgf23 / Klotho ) and single Fgf23, Klotho, and VDR mutants. As expected, 4‐week‐old Fgf23, Klotho, and Fgf23 / Klotho knockout mice were hypercalcemic and hyperphosphatemic, whereas VDR, Fgf23 /VDR, and Klotho /VDR mice on rescue diet were normocalcemic and normophosphatemic. Serum levels of calcium, phosphate, and sodium did not differ between 4‐week‐old triple Fgf23 / Klotho /VDR and double Fgf23 /VDR or Klotho /VDR knockout mice. Notably, 3‐month‐old Fgf23 / Klotho /VDR triple knockout mice were indistinguishable from double Fgf23 /VDR and Klotho /VDR compound mutants in terms of serum calcium, serum phosphate, serum sodium, and serum PTH, as well as urinary calcium and sodium excretion. Protein expression analysis revealed increased membrane abundance of sodium‐phosphate co‐transporter 2a (NaPi‐2a), and decreased expression of sodium‐chloride co‐transporter (NCC) and transient receptor potential cation channel subfamily V member 5 (TRPV5) in Fgf23 / Klotho /VDR, Fgf23 /VDR, and Klotho /VDR mice, relative to wild‐type and VDR mice, but no differences between triple and double knockouts. Further, ex vivo treatment of live kidney slices isolated from wild‐type and Klotho /VDR mice with soluble Klotho did not induce changes in intracellular phosphate, calcium or sodium accumulation assessed by two‐photon microscopy. In conclusion, our data suggest that the main physiological function of Klotho for mineral homeostasis in vivo is its role as co‐receptor mediating Fgf23 action. © 2017 American Society for Bone and Mineral Research.